New Insights into the Links between ESP and Geomagnetic Activity - RYAN, ADRIAN (Journal of Scientific Exploration, 2010)
A database of 343 free-response ESP trials conducted at centers in the U.K. was constructed in order to test the hypothesis that the relatively fast varying components of geomagnetic activity, geomagnetic pulsations, might be driving the reported associations between ESP, geomagnetic activity and local sidereal time. Local geomagnetic field measurements taken at 1- second intervals during 99 trials, and at 5-second intervals during 244 trials, were converted by fast Fourier transform into power within five frequency bands. Two patterns were observed: ESP was found to succeed only during periods of enhanced pulsation activity within the 0.2–0.5 Hz band, but ESP effect was absent during the most disturbed periods of activity in the 0.025–0.1 Hz band. The pattern of ESP effect by local sidereal time was similar to that found by Spottiswoode (1997b), and this shape was found to be attributable to the pattern of ESP results by pulsation activity in the 0.2–0.5 Hz band. The observed patterns were demonstrated to have excellent explanatory power in terms of accounting for findings previously reported in the literature. Keywords: ESP—geomagnetic activity—geomagnetic pulsations—local sidereal time